DIGITAL ACCOUNTING - Sharobiddinov Ahrorbek Qosimjon ugli, (Лучшие интеллектуальные исследования, 2024)
Abstract. The nature, advantages, and disadvantages of forms of accounting organization based on innovative technologies in the conditions of the digital economy are described. the essence of the concept of the digital economy and the conveniences and disadvantages of using software, national technologies, and blockchain technologies used in accounting in foreign countries at the present time are researched.